How large is the housing wealth effect? A new approach - Christopher D. Carroll; Misuzu Otsuka; Jirka Slacalek (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
This paper presents a simple new method for estimating the size of 'wealth effects' on aggregate consumption. The method exploits the well-documented sluggishness of consumption growth (often interpreted as 'habits' in the asset pricing literature) to distinguish between short-run and long-run wealth effects. In U.S. data, we estimate that the immediate (next-quarter) marginal propensity to consume from a 1 change in housing wealth is about 2 cents, with a final long-run effect around 9 cents. Consistent with several recent studies, we find a housing wealth effect that is substantially larger than the stock wealth effect. We believe that our approach is preferable to the currently popular cointegrationbased estimation methods, because neither theory nor evidence justifies faith in the existence of a stable cointegrating vector.
urn:nbn:de:hebis:30-38092
Keywords: E21; E32; C22; 330; Housing Wealth; Wealth Effect; Consumption Dynamics; Asset Price Bubbles; Immobilien; Eigentum; Vermögenseffekt; Gesamtwirtschaftlicher Konsum; USA